SU(2) Quantum Yang-Mills thermodynamics: some theory and some applications - Hofmann, Ralf (Universe, 2018)
In the first part of this talk, we review some prerequisites for and essential arguments involved in the construction of the thermal-ground-state estimate underlying the deconfining phase in the thermodynamics of SU(2) Quantum Yang–Mills theory and how this structure supports its distinct excitations. The second part applies deconfining SU(2) Yang–Mills thermodynamics to the Cosmic Microwave Background in view of (i) a modified temperature-redshift relation with an interesting link to correlation-length criticality in the 3D Ising model, (ii) the implied minimal changes in the dark sector of the cosmological model, and (iii) best-fit parameter values of this model when confronted with the spectra of the angular two-point functions temperature-temperature (TT), temperature-E-mode-polarisation (TE), E-mode-polarisation-E-mode-polarisation (EE), excluding the low-l physics. The latter, which so far is treated in an incomplete way due to the omission of radiative effects, is addressed in passing.
This article belongs to the special issue selected papers from the 7th International Conference on New Frontiers in Physics (ICNFP 2018)
Gesehen am 19.11.2019